FORMULASI DAN UJI SIFAT FISIK PERMEN EDIBLE FILM EKSTRAK ETANOL DAUN SAGA (Abrus precatorius L) - Rina Widiastuti; Nur Ismiyati; Syaikha Fahrun Nisa (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
The fungus Candida albicans is one of the causes of mouth ulcer whose growth can be inhibited through the activity of saga leaf extract which contains saponin and flavonoid compounds. One of the efforts to facilitate the use of ethanolic extract of saga leaves is to make it into edible film candy preparations. This study aims to evaluate the physical properties of edible film candies containing an ethanol extract of saga leaf with varying concentrations of hydroxypropyl methylcellulose (HPMC). The ethanol extract of saga leaves was prepared using the maceration method with 70% alcohol, resulting in a 5% concentration of ethanol extract of saga leaves. The HPMC concentrations used varied between 3.5%, 2.5%, and 1.5%. Subsequently, the resulting edible film underwent physical property tests, including organoleptic evaluations, moisture content, pH, thickness, weight determination, and dissolution time. The analysis revealed that the edible film exhibited a thin shape and a blackish-green color, along with a distinctive aroma of the extracts and sweet, bitter, and minty flavors. The pH of the edible film was 6, with a moisture content of less than 20%, and a fold resistance of less than 100. Moreover, it only melted without dissolving. Statistical analysis demonstrated a significant difference in the thickness and weight of the edible film among the variations in HPMC concentration. In conclusion, the comparison of HPMC concentration affects the physical properties of edible film candy containing ethanol extract of saga leaves, and HPMC concentration of 2.5% is a suitable choice to meet the requirements of edible film according to the Indonesian National Standard (SNI).